PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN GAYA KEPEMIMPINAN, MOTIVASI DAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING - Budiman, Caesar Arif; Sari, Ria Nelly; Ratnawati, Vince (SOROT, 2014)
this study aimed to determine (1) the effect of budgetaryparticipation on managerial performance in the preparation of thebudget, (2) the effect of leadership style on the relationship betweenbudgetary participation and managerial performance, (3) the effect ofmotivation on the relationship between budgetary participation andmanagerial performance, and (4) the effect of job relevantinformation on the relationshipbetween budgetary participation andmanagerial performance. The subjects of this study are all managersin bank riau kepri. The data was collected by distributingquestionnaires to 138 respondents, but only 85 respondents who fillout the questionnaires. The analysis tool is using Partial Least Square(PLS) program version 2.0. The result show that budgetaryparticipation has positive and significant effect on managerialperformance. Furthermore, job relevant information has positive andsignificant effect with budgetary participation and the managerialperformance. The data of this study failed to support the mediatingrate of leadership style and motivation on the relationship betweenbudgetary participation and the managerial performance.